2016
DOI: 10.1109/tmi.2015.2501832
|View full text |Cite
|
Sign up to set email alerts
|

Development of Real-Time Magnetic Resonance Imaging of Mouse Hearts at 9.4 Tesla— Simulations and First Application

Abstract: A novel method for real-time magnetic resonance imaging for the assessment of cardiac function in mice at 9.4 T is proposed. The technique combines a highly undersampled radial gradient echo acquisition with an image reconstruction utilizing both parallel imaging and compressed sensing. Simulations on an in silico phantom were performed to determine the achievable acceleration factor and to optimize regularization parameters. Several parameters characterizing the quality of the reconstructed images (such as sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…In particular, we prove an ( ) 2 1 k  convergence rate of the value of reduced cost functional, where k is the number of proximal iterations. This notion of convergence is used in l 1 -based optimization and in some application fields [14]. We remark that many arguments in our analysis are similar to those presented in the finite-dimensional case.…”
Section: Introductionsupporting
confidence: 52%
“…In particular, we prove an ( ) 2 1 k  convergence rate of the value of reduced cost functional, where k is the number of proximal iterations. This notion of convergence is used in l 1 -based optimization and in some application fields [14]. We remark that many arguments in our analysis are similar to those presented in the finite-dimensional case.…”
Section: Introductionsupporting
confidence: 52%
“…Haji‐Valiyadeh et al 27 applied a balanced steady‐state free precession sequence (b‐SSFP) with tyGRASP in RT imaging. For preclinical research, Wech et al 21 investigated the application of radial generalized autocalibrating partially parallel acquisitions (GRAPPA) with large GA (111.25°) in RT imaging. In our study, we applied the tyGRASP to nongated RT functional imaging and first‐pass perfusion imaging with single heartbeat temporal resolution in the Nexn‐induced heart failure mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the acquisition times in the minute range for a single slice still limit its application, eg for pharmacological stress or first‐pass perfusion imaging. To reduce acquisition times, the application of real‐time (RT) methods not demanding any gating (real time) for the rapid and continuous acquisition of image datasets, such as parallel imaging, 12–14 k‐t acceleration methods, 15–17 and compressed sensing (CS), 18–20 have been suggested and initially evaluated in mice 21 . Radial trajectories have shown favorable properties for RT imaging by their intrinsic low motion artifact level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of combining GROG with iterative non-Cartesian image reconstruction has been investigated in several studies. For example, it has been applied to non-Cartesian MR parameter mapping (30), real-time mouse imaging (31), dynamic contrast-enhanced MRI (32,33), and cardiac perfusion imaging (34). These results showed that GROG enables remarkable reduction of reconstruction time without sacrificing image quality or temporal fidelity.…”
Section: Introductionmentioning
confidence: 99%